Implementasi Pendekatan Saintifik Pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti: Implementation of a Scientific Approach in Islamic Religious Education Subjects and Morals - Muchamad Syaifudin; Masyhadi Masyhadi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
The purpose of this study is to look at the planning, application, and evaluation in Scientific Learning. The problems that occur are planning that has not been prepared by the teacher, the application of conventional and evaluation that has not been structured with the system of approx. The approach used is a qualitative approach, while if viewed from the point of view of the ability or possibility of research can provide information or explanation then this study includes research including descriptive research. The results showed that the implementation of Islamic education with a scientific approach in elementary school Curahdukuh II is preparing a learning tool in the form of annual programs, semester programs, syllabus, and lesson plans. The method used in the implementation of learning carried out by teachers of Islamic education with a scientific approach in elementary school Curahdukuh II includes three main stages, namely preliminary activities, core activities (observe, ask, reason, try, and communicate), and closing activities. As well as the assessment and evaluation of learning outcomes implemented by teachers of Islamic education with a scientific approach in the state Elementary School Curahdukuh II is the evaluation of learning processes and outcomes.